Evaluating Bureaucratic Simplification: Effects on Public Service Quality in Lampung Province, Indonesia - Yenita Anggraini; Nandang Alamsah Deliarnoor; Andi Kasman (Journal of Social Work and Science Education, 2026)
Bureaucratic simplification represents a strategic government effort to enhance organizational effectiveness and public service quality. This study analyzes the influence of bureaucratic simplification policy implementation on public service quality at the Investment and One-Stop Integrated Service Agency (DPMPTSP) of Lampung Province, Indonesia. Using a quantitative survey design, data were collected from 150 service recipients selected through random sampling. Policy implementation was measured through Mazmanian and Sabatier’s (1983) framework (tractability of problems, ability of statute to structure implementation, and nonstatutory variables), while service quality was measured using the five-dimensional SERVQUAL model (tangibles, reliability, responsiveness, assurance, empathy). Due to non-normal distribution of independent variables, Spearman Rank Correlation was employed. Results indicate that all three implementation dimensions significantly and positively influence service quality: tractability of problems (r = 0.329, p < 0.01), ability of statute to structure implementation (r = 0.418, p < 0.01), and nonstatutory variables (r = 0.396, p < 0.01), with total implementation showing r = 0.417 (p < 0.01). The regulatory framework dimension emerged as the strongest determinant of service quality improvement. The study contributes to bureaucratic reform literature by empirically testing the Mazmanian-Sabatier framework in a regional one-stop service context. Limitations include cross-sectional design and single-agency focus. Findings suggest that strengthening regulatory clarity and coordination mechanisms should be prioritized in bureaucratic simplification efforts.